EFFECTIVE PAIRWORK STRATEGIES TO ENHANCE SAUDI PRE-INTERMEDIATE COLLEGE STUDENTS’ LANGUAGE PRODUCTION IN SPEAKING ACTIVITIES - Zohairy, Said (European Scientific Journal, ESJ, 2014)
Classroom dynamics remained one of the most critical areas in the field of English language teaching and methodology. Pairwork and pairing strategies have been the focus of this study in regards with increasing language production in speaking activities for Saudi pre-intermediate college students. Participants in this study are university-preparatory-year students (60 students) and EFL/ESL teachers (15 teachers) in the same program. Data collection included an attitudinal questionnaire to investigate students’ attitude towards various strategies of pairing up students for speaking activities. In addition, a semi-constructed interview was used to examine teachers’ perception of the importance of pairwork in classrooms and the effectiveness of various strategies. Moreover, the researcher acted as an overt observer to measure students’ production during various pairing strategies in an overt-focused observation. Researcher’s findings showed some discrepancies between teachers’ and students’ perception of pairwork strategies. Saudi students prefer to pair up with a higher-level student (L-H) as they tend to rely on colleagues to complete tasks rather than asking teacher to help. On the contrary, teachers prefer same-level pairing to provide equal learning opportunities for all students.